Synthesis of In0.1Ga0.9N/GaN structures grown by MOCVD and MBE for high speed optoelectronics. Issue 23 (7th June 2016) - Alshehri, Bandar; Dogheche, Karim; Belahsene, Sofiane; Janjua, Bilal; Ramdane, Abderrahim; Patriarche, Gilles; Ng, Tien-Khee; S-Ooi, Boon; Decoster, Didier; Dogheche, Elhadj
ABSTRACT: In this work, we report a comparative investigation of Inx Ga1-x N (SL) and Inx Ga1-x N/GaN (MQW) structures with an indium content equivalent to x=10%. Both structures are grown on (0001) sapphire substrates using MOCVD and MBE growth techniques. Optical properties are evaluated for samples using PL characteristics. Critical differences between the resulting epitaxy are observed. Microstructures have been assessed in terms of crystalline quality, density of dislocations and surface morphology. We have focused our study towards the fabrication of vertical PIN photodiodes. The technological process has been optimized as a function of the material structure. From the optical and electrical characteristics, this study demonstrates the benefit of InGaN/GaN MQW grown by MOCVD in comparison with MBE for high speed optoelectronic applications.